El proceso de atención de enfermería escolar con énfasis a patrones alimentarios disfuncionales relacionados con riesgo de desequilibrio nutricional, en escolares del 7mo Año de Básica paralelo “B” de la escuela Julio María Matovelle - Gálvez Rodríguez, Mayra Vanessa (2014)
This research was done in order to implement the Nursing Care Process, among the objectives is to investigate the eating habits in / 7th school year basic education parallel " B" school Julio María Matovelle , promoting healthy nutrition, with an intervention program for school nursing health promotion and disease prevention and include family and teachers on healthy nutritional counseling. The study was descriptive with the intervention was applied to 25 children 7th "B" school "Julio María Matovelle " between the techniques and tools an instrument with 11 functional patterns Marjory Gordon was used , the growth curves MSP and development , online home visits , based on which it was found that the pattern is altered Nutrition - Metabolic . The results obtained by 20 % of children with nutritional imbalance by excess consumption 83.2 carbohydrates in your regular diet , there was a further 80% of children with impaired dentition associated tooth brushing , based on the nutritional imbalance excess ( 00001 ) Impaired dentition ( 00048 ) , ineffective health Maintenance ( 00099 ) which were created following nursing diagnoses . Activities Nursing executed were: shop healthy eating, talk food preparation, lunchboxes and healthy school kiosk, educational lecture dental health, open house with healthy school lunchbox theme aimed at parents, schools and teachers KEYWORDS: nursing process, excess nutritional imbalance, impaired dentition